Association between Bmi1 and clinicopathological status of esophageal squamous cell carcinoma - He, Xiao-Ting (The WJG Press, 2009)
AIM: To investigate the clinicopathological roles of Bmi1 in esophageal squamous cell carcinoma (ESCC). METHODS: Quantitative real-time polymerase chain reaction and immunohistochemical staining for Bmi1 were performed in cancerous and adjacent non-cancerous paraffin-embedded esophageal specimens. RESULTS: The Bmi1 expression level was unaffected by gender and age. The level of Bmi1 mRNA in ESCC was significantly higher than that in the adjacent non-cancerous tissues (2.181 ± 2.158 vs 0.931 ± 0.894, P = 0.0152), and its over-expression was aggressively associated with lymph node metastasis (3.580 ± 2.487 vs 1.703 ± 0.758, P = 0.0003), poorer cell differentiation (P = 0.0000) and advanced pathological stage (3.827 ± 2.673 vs 1.590 ± 0.735, P = 0.0001). The patients were divided into high-expression and low-expression groups based on the median expression level of Bmi1 mRNA, and a shorter overall survival time in the former group was observed. Immunohistochemistry for Bmi1 oncoprotein showed diffusely positive, focally positive and negative expression in 44, 16 and 10 of 70 ESCC cases, respectively, compared with three, two and five of 10 adjacent non-cancerous cases (P = 0.027). The positive rate of the oncoprotein in samples of histological grade III was higher than that of grade II (P = 0.031), but its expression had no relation to the lymph node metastasis and pathological staging. In 70 ESCC samples, Bmi1 showed high intense expression in the cytoplasm and less or even no expression in the nucleus. CONCLUSION: Bmi1 was over-expressed in ESCC. Increased Bmi1 mRNA expression was significantly associated with ESCC progression, and the oncoprotein was largely distributed in the cytoplasm of tumor cells.